Review of insulin‐associated hypoglycemia and its impact on the management of diabetes in Southeast Asian countries. Issue 5 (4th May 2017) - Goh, Su‐Yen; Hussein, Zanariah; Rudijanto, Achmad
Abstract : Insulin‐associated hypoglycemia is a worldwide concern, not least in South East Asia where there is a paucity of information regarding the true rates and impact of hypoglycemia. This review discusses how the etiological and cultural differences between South East Asian populations and Western populations (from which most standard treatment guidelines have been developed) might require bespoke guidelines to be drawn up for insulin use in South East Asians to better enable them to avoid and deal with hypoglycaemia. Abstract: Although the incidence of diabetes is rising in Southeast Asia, there is limited information regarding the incidence and manifestation of insulin‐associated hypoglycemia. The aim of the present review was to discuss what is currently known regarding insulin‐associated hypoglycemia in Southeast Asia, including its known incidence and impact in the region, and how the Southeast Asian population with diabetes differs from other populations. We found a paucity of data regarding the incidence of hypoglycemia in Southeast Asia, which has contributed to the adoption of Western guidelines. This might not be appropriate, as Southeast Asians have a range of etiological, educational and cultural differences from Western populations with diabetes that might place them at greater risk of hypoglycemia if not managed optimally. For example, Southeast Asians with type 2 diabetes tend to be younger, with lower body mass indexes than their Western counterparts, and the management of type 2 diabetes with premixed insulin preparations is more common in Southeast Asia. Both of these factors might result in higher rates of hypoglycemia. In addition, Southeast Asians are often poorly educated about hypoglycemia and its management, including during Ramadan fasting. We conclude there is a need for more information about Southeast Asian populations with diabetes to assist with the construction of more appropriate national and regional guidelines for the management of hypoglycemia, more closely aligned to patient demographics, behaviors and treatment practices. Such bespoke guidelines might result in a greater degree of implementation and adherence within clinical practice in Southeast Asian nations.